Improvement of gastroesophageal reflux disease in Japanese patients with spinal kyphotic deformity who underwent surgical spinal correction. Issue 1 (30th September 2015) - Sugimoto, Mitsushige; Hasegawa, Tomohiko; Nishino, Masafumi; Sahara, Shu; Uotani, Takahiro; Ichikawa, Hitomi; Kagami, Takuma; Sugimoto, Ken; Yamato, Yu; Togawa, Daisuke; Kobayashi, Sho; Hoshino, Hironobu; et al.
Abstract : Background and Aim: Spinal kyphotic deformity occasionally results in gastroesophageal reflux disease (GERD). The effects of acid reflux on the esophagus in kyphotic patients are unclear, however, and it is unknown whether acid reflux, endoscopic GERD, and reflux‐related symptoms improve following surgical spinal correction in these patients. Herein, we investigated the characteristics of GERD in kyphotic patients and the improvement in GERD following surgical correction. Methods: In 48 patients with severe kyphotic deformity scheduled for surgical spinal correction, we conducted esophagogastroduodenoscopy, 24‐h pH monitoring and three questionnaire surveys, including the frequency scale for the symptoms of GERD (FSSG). We repeated these measurements after surgical correction and compared pre‐ and post‐surgery values. Results: Of 48 patients, 70.8% [95% CI: 55.9–83.0%, 34/48] had endoscopically evaluated esophageal mucosal injury. Regarding pH before surgery, 64.9% (CI: 47.5–79.8%, 24/37) had abnormal acid reflux (intraesophageal pH < 4 more than 5% of the time). FSSG score was significantly associated with the severity of GERD, and the positive rate was 52.6% (CI: 35.8–69.0%, 20/38). Following surgical correction, esophageal mucosal injury improved endoscopically in 90% of patients, and median total FSSG score significantly decreased from 8 (0–30) to 5 (0–19) ( P  = 0.005). Regarding pH after surgery, prevalence of abnormal acid reflux decreased from 66.7% (95% CI: 41.0–86.7%) to 33.3% (95% CI: 13.3–59.0%) ( P  = 0.045). Conclusion: Surgical spinal correction in kyphosis patients improves not only kyphotic deformity‐related disorders but also esophageal mucosal injury, abnormal acid reflux, and reflux‐related symptoms.